Modern Portfolio Theory and Investment Analysis - Elton, Edwin J. (Hoboken: J. Wiley & Sons, 2003)
Covers the characteristics and analysis of individual securities as well as the theory and practice of optimally combining securities into portfolios. Stressing the economic intuition behind the subject matter, this book presents concepts of investment analysis and portfolio management.
Includes Index.
Keywords: Analyse financière; Business enterprises Finance; Corporations Finance